Characteristics of laccase producing Trametes maxima CPB30 and its application in decolorization of dye polluted water - Lam, Duong Minh; Chien, Truong Thi (Academia Journal of Biology, 2014)
The strain Trametes maxima CPB30 isolated from Cuc Phuong National Park is strongly laccase producing fungus. Among 8 culture media used for laccase screening, potato dextrose agar (PDA) was the most preferable to the strain for produging laccase. The laccase produced by T. maxima CPB30 strongly decolorized of RBBR. Apart from the role of a substrate of the enzyme, RBBR had a role of laccase producing inducer of T. maxima CPB30. The growth rate and laccase producing ability of T. maxima CPB30 is not much affected by pH value of the growing medium, however, the most suitable pH condiction is acidic. This is one of the advantages that the strain possesses in order to use in environmental applications. The strain T. maxima CPB30 has high potential of application in dye decolorization and detoxification.